2024
DOI: 10.1101/2024.03.14.585048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell view of tumor microenvironment gradients in pleural mesothelioma

Bruno Giotti,
Komal Dolasia,
William Zhao
et al.

Abstract: Immunotherapies have shown great promise in pleural mesothelioma (PM), yet most patients still do not achieve significant clinical response, highlighting the importance of improving understanding of the tumor microenvironment (TME). Here, we utilized high-throughput, single-cell RNA-sequencing to de novo identify 54 expression programs and construct a comprehensive cellular catalogue of the PM TME. We found four cancer-intrinsic programs associated with poor disease outcome and a novel fetal-like, endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…While previous studies in bulk RNA identified a continuous EM gradient across samples (Alcala et al, 2019; Blum et al, 2019), these analyses were unable to identify which cell components were driving this phenotype. The concordance between bulk and malignant cell-specific EM signatures demonstrated in the present study suggests that previous findings in bulk tissue were largely representative of malignant cell variation and is consistent with another recent PM scRNA-seq study (Giotti et al, 2024). Furthermore, we describe a new malignant cell state, termed uncommitted, in PM most frequently isolated in biphasic tumor samples.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While previous studies in bulk RNA identified a continuous EM gradient across samples (Alcala et al, 2019; Blum et al, 2019), these analyses were unable to identify which cell components were driving this phenotype. The concordance between bulk and malignant cell-specific EM signatures demonstrated in the present study suggests that previous findings in bulk tissue were largely representative of malignant cell variation and is consistent with another recent PM scRNA-seq study (Giotti et al, 2024). Furthermore, we describe a new malignant cell state, termed uncommitted, in PM most frequently isolated in biphasic tumor samples.…”
Section: Discussionsupporting
confidence: 92%
“…While mutations remove the checkpoint on proliferation, it may be that non-malignant cells provide the fuel for proliferation, where mesenchymal cells tend to be driven by GAS6-AXL and epithelioid tumors by HBEGF-EGFR signaling. Notably, GAS6-AXL signaling has been previously identified as a an important EMT gene in PM (Engelsen et al, 2022; Ou et al, 2011)and AXL was recently described as associated with sarcomatoid malignant cell module gene expression in another PM scRNA-seq study(Giotti et al, 2024). We also identify inhibition of WNT as a potential mechanism for maintaining an uncommitted cell state, given the identification of SFRP2, HHIP , DKK1 , DKK2 , and DKK3 as either signature biomarkers or significantly differentially expressed in in uncommitted cells.…”
Section: Discussionmentioning
confidence: 99%